Advancing Novel HIV Prevention Intervention Research with MSM—Meeting Report - Grossman, Cynthia I. (Association of Schools of Public Health, 2011)
HIV continues to exact an enormous toll on society and to disproportionately affect gay and bisexual men and other men who have sex with men (MSM). Innovative prevention interventions are needed to reverse this trend. In August 2009, the U.S. National Institute of Mental Health and the Centers for Disease Control and Prevention convened a meeting of scientists, community representatives, advocates, and federal partners to discuss innovative prevention-intervention science. The meeting was structured to maximize discussion of (1) healthy sex interventions, (2) community and structural interventions, (3) integrated biomedical and behavioral interventions, and (4) interventions to improve uptake of HIV testing. Presentations and discussion focused on research gaps in designing risk-reducing and sexual health-promoting interventions for MSM, including interventions to address mental health, substance use, disclosure, and stigma. This article summarizes the meeting proceedings, highlights key points, and outlines future directions.